Regulasi Fraud Order Transportasi Online Dalam Kode Etik Perusahaan Dan Peraturan Perundang-Undangan Di Indonesia; Studi Pada Pt Grab Indonesia - Ahmad Boby Permana; Indra Rahmatullah (JOURNAL of LEGAL RESEARCH, 2019)
Abstract.The act of fraud committed by the driver's partner is considered a weakness in the field of electronic transaction services. Handling the system and code of ethics carried out by PT Grab Indonesia for fraud perpetrators by preventing and minimizing fraud that can harm the company. The implementation of code of conduct sanctions is a result of defaults that have been carried out by driver partners. This research uses qualitative research with a normative approach. The method used is library research by reviewing the laws and regulations. The conclusion from the results of the study that the code of ethics owned by PT. Grab as a guideline and a form of security from fraud through internal and external supervision involving the community.Keywords: Regulation, fraud order, code of ethics, transportation, online